Investigating Upper Atmospheric Joule Heating Using Cross‐Combination of Data for Two Moderate Substorm Cases. Issue 8 (13th August 2018) - Kalafatoglu Eyiguler, E. C.; Kaymaz, Zerefsan; Frissell, Nathaniel A.; Ruohoniemi, J. M.; Rastätter, Lutz
Abstract: In this work, empirical relationships based on indices (AE, IL, and KP), an empirical model (Weimer‐2005), coupled space weather models (BATS‐R‐US+CRCM/RCM), and combinative methods (using data from SuperDARN for electric field and OVATION PRIME+IRI combination for the conductances) are employed to investigate the Joule heating (JH) variability during two isolated substorms on 8 March 2008. The results are compared according to substorm phases, magnetic local time sectors, magnetic latitudes, role of electric fields, ionospheric conductances, and neutral wind. Qualitatively, all methods exhibit similar variations in the estimated JH rates. AE‐dependent methods and the Weimer‐2005 model show the highest JH rates. The response of AE to the elevated Epsilon levels is found to be delayed up to 50 min, whereas the onsets and variations in the other methods are concurrent with Epsilon. The combination of OVATION Prime+IRI and SuperDARN provides values close to the (Foster et al., 1983, https://doi.org/10.1029/JA088iA06p04885 ) suggesting that it is representative enough to use for estimating the JH. The OVATION Prime+IRI and SuperDARN method can provide JH at any point in the solar cycle based on dynamic solar wind input. BATSRUS/CRCM conductances and electric fields are higher than BATSRUS/RCM leading to 2.5 times as much JH as estimated by BATSRUS/RCM on average. Neutral winds are found to comprise an overall 15% of total JH with a maximum of 25% in dusk sector during the expansion phase. We discuss that W05 and AE‐dependent methods overestimate the JH rates during the solar minimum since they are constructed using solar maximum data. Plain Language Summary: Ionized particles and neutrals reside together in the outer layers of the Earth's atmosphere. During geomagnetic activity such as magnetospheric substorms and geomagnetic storms, the solar wind energy input to the Earth's upper atmosphere increases. Consequently, the ions and neutrals in the ionosphere collide more often. Joule heating (JH) is the frictional heating in the upper atmosphere resulting from the interaction between the ions and neutrals. This interaction causes the upper atmosphere to expand, thus increases the drag on the satellites in low Earth orbit. In this paper, we present the alternative methods used in the literature to calculate JH, compare their results, and bring out their success and/or failures so that these methods can be used in case of limited number or absence of the parameters based on the global observations. We find that using electric field provided by Super‐Dual Auroral Radar Network and height‐integrated conductivities that are derived from empirical IRI2012 and OVATION Prime models, JH can be approximated reasonably well during the solar minimum with 2‐min resolution. We discuss that some of the widely used methods in finding JH overestimate the solar minimum JH magnitudes as they were constructed using solar maximum data. Key Points: OVATION Prime+IRI and SuperDARN (OIS) combination can be used at any point in the solar cycle to validate the models The OIS and BATSRUS/CRCM JH show the best agreements during the expansion phase and when SuperDARN had data in the midnight sector Weimer‐2005 and AE‐dependent methods overestimate the JH rates during solar minimum as they were constructed using solar maximum data